Hydrogels derived from human chorionic membrane as an innovative platform for 3D cell culture - Martins, Elisa Alexandra Gonçalves (2023)
Regenerative medicine and tissue engineering have emerged as alternatives to therapies currently used in the treatment and replacement of damaged tissues or organs, due to the very limited capacity of the human body to regenerate. This area combines the culture of cells in biomaterials and the presence of signals. In native tissue, cells are surrounded by an extracellular matrix (ECM) composed of several proteins, glycosaminoglycans and soluble factors. ECM is very important in the cellular response, as it influences processes such as migration, proliferation and differentiation. Thus, an effort has been made to create materials that mimic this function. The human placenta is a virtually unlimited source of ECM, without associated ethical issues, immunoprivileged, biocompatible and capable of healing. In addition, the successful use of fetal membranes as an allograft has been reported in the literature and more recently the chorionic membrane has been described as effective in periodontal regeneration. In addition to the base material, the used morphology is also important. Hydrogels are a unique class of materials in terms of their ability to mimic ECM. They are 3D hydrophilic polymeric networks capable of capturing large amounts of water, allowing cell fixation and migration, exchange of nutrients, oxygen and cellular waste. However, most hydrogels produced from decellularized ECM have low mechanical properties, since these must mimic the native tissue. Thus, the objective of this work is to produce, as far as we know, for the first time, hydrogels derived from photocrosslinkable human chorionic membrane (CM) with adjustable mechanical properties, for the 3D culture of cells. In this work, CM prepolymers were produced by the addition of methacrylic anhydride, with two degrees of modification: one with a lower degree (CMMA100) and another with a higher degree of modification (CMMA250). By adding a photoinitiator to these prepolymers and in the presence of light with a specific wavelength it is possible to produce hydrogels. Quantifications of some of the most important ECM proteins allowed to verify their retention in the obtained material. The evaluation of the mechanical properties allowed to realize that it was possible to produce robust hydrogels and whose mechanical properties and water absorption capacity vary with their concentration and which are in the range of most human tissue elastic modulus. Moreover, it was possible to verify that CMMA hydrogels allowed the culture of cells that proliferated and remained viable for at least 7 days. The results obtained so far suggest that these CMMA based hydrogels have potential for 3D cell culture.